# Solve for x. 2x^2-9x+7=0

### 2 Answers | Add Yours

You need to find the solutions to the given quadratic equation, hencem you may use quadratic formula such that:

`x_(1,2) = (-b+-sqrt(b^2 - 4ac))/(2a)`

Identifying the coefficients a,b,c yields:

`a = 2, b = -9, c = 7`

`x_(1,2) = (9 +- sqrt((-9)^2 - 4*2*7))/(2*2)`

`x_(1,2) = (9 +- sqrt(81 - 56))/4`

`x_(1,2) = (9 +- sqrt25)/4 => {(x_1 = (9 + 5)/4),(x_2 = (9 - 5)/4):}`

`x_1 = 7/2; x_2 = 1`

**Hence, evaluating the solutions to quadratic equation, yields **`x_1 = 7/2; x_2 = 1.`

`2x^2-9x+7=0`

Let us factorize it by spliting middle term

`2x^2-7x-2x+7=0`

`x(2x-7)-1(2x-7)=0`

`(2x-7)(x-1)=0`

`So either 2x-7=0 or x-1=0`

`2x-7=0`

`x=7/2 `

`x=1`